PERBEDAAN KADAR HEMOGLOBIN PADA PASIEN SEBELUM DAN SESUDAH OPERASI CAESAR - Nosa Ika Cahyariza; Hariyanto Hariyanto; Chalies Diah Pratiwi (Medical Laboratory Analysis and Sciences Journal, 2020)
Caesarean section is a process to remove a fetus or baby through an incision in the abdominal wall and upper uterus because a normal birth process is not possible. The process by Caesarean section requires careful preparation because the result can be bleeding. One of the tests before and after Caesarean section is checking the hemoglobin level. The purpose of this study was to determine the differences in hemoglobin levels before and after Caesarean section. This research is a quantitative analysis. Sampling was conducted in April 2018 at RSIA Fauziah Tulungagung and hemoglobin levels were checked using the Cyanmehemoglobin method at the STIKes Hutama Abdi Husada Tulungagung Pathology Laboratory. The population of this study were all pregnant women who underwent a Caesarean section at RSIA Fauziah Tulungagung using a total sampling technique of 30 samples. The instrument used was a photometer, then the data was processed using SPSS 16 software and analyzed using the Paired T-Test technique. The results of research conducted on 30 samples of Caesarean section patients obtained an average hemoglobin level before Caesarean section 13.13 g / dl and an average hemoglobin level after Caesarean section 12.06 g / dl after the Paired T-Test was obtained. 0.002 <0.05. It can be concluded that there is a significant difference between the hemoglobin levels before and after Caesarean section. Bleeding during Caesarean section causes hemoglobin levels in pregnant women to decrease.